Benchmark calculations of the 2D Rydberg spectrum of lithium. (18th June 2021) - Stanke, Monika; Palikot, Ewa; Sharkey, Keeper L.; Adamowicz, Ludwik
Abstract : The recently implemented algorithm for calculating the leading relativistic corrections for D states of an atom with an arbitrary number of electrons is used to perform calculations of the lowest eleven 2 D Rydberg states of lithium. The corrections are obtained as expectation values of the corresponding relativistic operators with the non-relativistic wave functions expanded in terms of all-electron explicitly correlated Gaussian (ECG) functions. The wave functions are generated using the standard variational method and the finite-nuclear-mass (FNM) approach. The non-linear parameters of the ECGs are variationally optimised using a algorithm that employs the analytical energy gradient determined with respect to these parameters. Infinite-nuclear-mass calculations are also performed. The calculated FNM state energies for 6 Li and 7 Li are used to calculate isotopic shifts of the inter-state transition energies. The calculated interstate transitions are in good agreement with the high-quality experimental results. GRAPHICAL ABSTRACT: UF0001